MicroRNA-21: A Critical Pathogenic Factor of Diabetic Nephropathy - Liu, Shuijiao; Wu, Weizhou; Liao, Jian; Tang, Fuqin; Gao, Ge; Peng, Jing; Fu, Xiujing; Zhan, Yuqin; Chen, Zhihui; Xu, Weifang; Zhao, Shankun (Frontiers in Endocrinology, 2022)
Diabetic nephropathy (DN), one of the most common and intractable microvascular complications of diabetes, is the main cause of terminal renal disease globally. MicroRNA-21 (miR-21) is a kind of miRNA early identified in human circulation and tissues. Mounting studies have demonstrated that miR-21 plays an important role in the development and progression of DN. This collaborative review aimed to present a first attempt to capture the current evidence on the relationship between miR-21 and DN. After a systematic search, 29 relevant studies were included for comprehensively and thoroughly reviewing. All these eligible studies reported that miR-21 was up-regulated in DN, whether in serum or renal tissues of human or animal models. MiR-21 exhibited its pathogenic roles in DN by forming a complex network with targeted genes (e.g. MMP-9, Smad7, TIMP3, Cdk6, FOXO1, IMP3, and MMP2) and the signaling cascades (e.g. Akt/TORC1 signaling axis, TGF-β/NF-κB signaling pathways, TGF-β/SMAD pathway, CADM1/STAT3 signaling, and AGE-RAGE regulatory cascade), which resulted in epithelial-to-mesenchymal transition, extracellular matrix deposition, cytoskeletal remodeling, inflammation, and fibrosis. This review highlights that miR-21 is a pivotal pathogenic factor in the development of DN. It may serve as an attractive potential diagnostic, prognostic, and predictive biomarker for DN in clinical practice after further confirmation with the clinicopathological features and molecular mechanisms of miR-21-mediated DN.